Linguagem, cognição e cultura: uma leitura em fenomenologia da prática educativa - Jucimara Rojas (EccoS – Revista Científica)
In this article we aim to address the issues of educational practices, contemplating the language, cognition and the culture as ways of construction of human beings throughout their existence. We seek to stress these theoretical elements in the phenomenological context, emphasizing the value aspect of learning process. We reaffirm human condition as the starting point to educationist/teacher in order to incorporate in his/her educational practices the phenomenological proposals as ways of seeking the true meaning of being, thinking and feeling of learners. We single out the importance of rethinking rooted attitudes, behaviors and beliefs which need to be broken, considering the new challenges that the contemporary world presents. We add, based on Merleau-Ponty, Martins, Bicudo, Aranha, Morin, Rojas, that the purposes of phenomenology send and suggest the perceptive, attentive, intentional and socializing appropriation of educationists, allying new looks to their practice, in a continuous search for sense effects in learning process.